UAV route planning for image 3D reconstruction - Wu Yuhao; An Zipeng (Dianzi Jishu Yingyong, 2019)
With the development of drones, three-dimensional reconstruction of UAV sequence images is receiving more and more attention. In order to make the captured sequence image completely reconstruct the 3D model of the mission area and the flight power consumption of the multi-rotor UAV is smaller, a multi-rotor UAV coverage path planning algorithm for image 3D reconstruction is proposed. For the convex polygon region, in order to meet the requirements of image overlap and time continuity, a multi-rotor UAV scanning route planning method based on the grating method is proposed and combined with the optimal scanning direction to minimize the number of turns. With the help of Gazebo simulation platform, it is verified that the power consumption of the multi-rotor UAV is smaller when the flight is obtained according to the algorithm of this paper, and the captured sequence image satisfies the requirements of the reconstruction task area three-dimensional model.